Analysis of mitochondrial and chloroplast genomes in two volvocine algae: Eudorina elegans and Eudorina cylindrica (Volvocaceae, Chlorophyta). Issue 2 (3rd April 2019) - Hu, Yuxin; Xing, Weiyue; Song, Huiyin; Liu, Guoxiang; Hu, Zhengyu
ABSTRACT: The colonial volvocine algae span the full range of organizational complexity, from four-celled species to multicellular species, and this group of algae is often used for the study of evolution. In recent years, many organelle genomes have been sequenced using the application of next generation sequencing technology; however, only a few organelle genomes have been reported in colonial volvocine algae. In this study, we determined the organelle genomes of Eudorina elegans and Eudorina cylindrica and analysed the organelle genome size, structure and gene content between these volvocine species. This provided useful information to help us understand the composition of colonial volvocine organelle genomes. Based on the chloroplast genome protein-coding genes, we conducted a phylogenomics analysis of the volvocine algae. The result revealed an unexpected phylogenetic relationship, namely, E. elegans is more closely related to Pleodorina starrii than to E. cylindrica . The substitution rate of volvocine algae was then calculated based on organelle genome protein-coding genes; our analysis suggested the possibility that the two Eudorina species may be under similar evolutionary pressure. Lastly, the synteny analysis of the mitochondrial genome showed that gene arrangements and contents are highly conserved in the family Volvocaceae, and the synteny analysis of the chloroplast genome indicated that the genus Eudorina may have experienced genomic changes.